Analysis of Special Civil Cases on Industrial Relations Disputes: A Case Study of Supreme Court Decision Number 347 K/Rev. Sus-PHI/2020 in the Perspective of International Civil Law: Industrial Relations Disputes - Agista, Yessa Ayu; Prastyanti, Rina Arum (West Science Law and Human Rights, 2025)
The case of the industrial relations dispute between PT Hevilift Aviation Indonesia and Joel Raymundo Alviar illustrates the legal complexity faced by companies and workers, especially in the context of the involvement of foreign nationals. The Supreme Court's Decision Number 347/K/Pdt. Sus-PHI/2020 is the focal point for analyzing the application of international civil law in employment relations in Indonesia. This article aims to provide an in-depth understanding of the legal basis underlying the award, as well as explore how international civil law is applied in these disputes. In addition, this article also examines the impact of the ruling on labor policy in Indonesia, including its implications for the protection of workers' rights and the policies of companies that employ foreign workersThe results show that the Supreme Court's ruling not only sets an important precedent in the settlement of industrial disputes, but also highlights the need for harmonization between national and international law in the context of employment. As such, this article contributes to a broader understanding of the interaction between international civil law and employment relations, as well as its implications for more effective labor policy in Indonesia.